2016
DOI: 10.1002/lsm.22548
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of port wine stains using Pulsed Dye Laser, Erbium YAG Laser, and topical rapamycin (sirolimus)—A randomized controlled trial

Abstract: Topical application of the commercially available solution of rapamycin (Rapamune 0.1%) as an adjuvant to PDL treatment does not appear to improve PWS blanching. Lasers Surg. Med. 49:104-109, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 37 publications
0
56
0
2
Order By: Relevance
“…11,[52][53][54][55] In a phase 2, randomized, double-blind, placebo-controlled clinical trial by Marqués et al, 52 23 patients tested topical sirolimus (1%) plus pulsed dye laser; the results suggested that topical sirolimus with pulsed dye laser was more effective than placebo or sirolimus alone or pulsed dye laser alone for the treatment of portwine stains in patients with Sturge-Weber syndrome. Greveling et al 11 published a randomized controlled trial of 14 patients comparing pulsed dye laser, pulsed dye laser plus sirolimus, pulsed dye laser plus erbium:yttriumaluminium-garnet laser plus sirolimus, and sirolimus monotherapy. The highest percentage skin clearance was achieved with pulsed dye laser alone, but there were no statistically significant differences between treatments.…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…11,[52][53][54][55] In a phase 2, randomized, double-blind, placebo-controlled clinical trial by Marqués et al, 52 23 patients tested topical sirolimus (1%) plus pulsed dye laser; the results suggested that topical sirolimus with pulsed dye laser was more effective than placebo or sirolimus alone or pulsed dye laser alone for the treatment of portwine stains in patients with Sturge-Weber syndrome. Greveling et al 11 published a randomized controlled trial of 14 patients comparing pulsed dye laser, pulsed dye laser plus sirolimus, pulsed dye laser plus erbium:yttriumaluminium-garnet laser plus sirolimus, and sirolimus monotherapy. The highest percentage skin clearance was achieved with pulsed dye laser alone, but there were no statistically significant differences between treatments.…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…The use of a different type of DDS did not yield similar effect as the Tixel in our report. Greveling et al compared PDL‐only treatment to PDL + rapamycin, PDL + Erbium YAG laser ablation without thermal of the stratum corneum + rapamycin, and rapamycin monotherapy, and reported that the highest percentage clearance was achieved with PDL‐only treatment, but there were no statistically significant differences between treatments (Greveling, Prens, & van Doorn, ).…”
Section: Discussionmentioning
confidence: 99%
“…julio -diciembre 2020 Gac Med Bol 2020; 43(2): podría prevenir la revascularización después del tratamiento con PDL; sin embargo Greveling y col. recientemente en un ensayo aleatorio demostraron que la aplicación tópica de la solución disponible en el mercado (Rapamune ® 0,1%) como un adyuvante al tratamiento PDL no parece mejorar el blanqueamiento de la lesión en el SSW, la Rapamicina oral podría tener resultados más prometedores, y se recomienda mayores investigaciones respecto a eficacia, efectos adversos y costo-efectividad 28 .…”
Section: G M Bunclassified
“…La Oxcarbazepina se asoció con menos efectos secundarios informados que otros antiepilépticos, por lo que puede ser preferible y se recomienda comenzar el tratamiento con Oxcarbazepina a menos que estén presentes características de crisis generalizadas 29 . El Topiramato a pesar de estar relacionado con desencadenar glaucoma agudo bilateral de ángulo cerrado empeorando el pronóstico en ciertos casos, no se asoció con signos relacionados al glaucoma en un análisis limitado de pacientes y los efectos secundarios informados del Valproato coincidieron con sus efectos conocidos, por lo que estos medicamentos podrían ser alternativas seguras para tratar la migraña y la epilepsia concomitantes, además de los triptanes y la Lamotrigina que también se han utilizado para este fin 4,28 . El ácido acetilsalicílico en dosis bajas (3 a 5 mg/kg/día) puede disminuir la frecuencia y la gravedad de los crisis epilépticas y de los episodios stroke-like 30 .…”
Section: G M Bunclassified